An Analysis of the Needs for Developing a CPS–EIS (Collaborative Problem Solving for Environmental Issue-Based Socio-Scientific Issues) Based Environmental Change E-Module as an Effort to Improve Students' Critical Thinking Skills - Endah Pratiwi; Baskoro Adi Prayitno; Umi Fatmawati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the need for developing an e-module based on Collaborative Problem Solving for Environmental Issue-Based Socio-Scientific Issues (CPS–EIS) on environmental change as an effort to improve students' critical thinking skills. This research employed a descriptive design with a needs analysis approach, conducted in December 2025 at a public high school in Karanganyar, involving 10th-grade students and biology teachers. Data were collected through Likert-scale questionnaires and interviews, then analyzed using percentage techniques and qualitative interpretation. The results indicate that although the level of difficulty of environmental change material was relatively low (42.57%), the current learning process remains less engaging and lacks structured problem-solving activities. Students showed a high need for multimedia integration (76.00%), strong readiness for collaboration (84.28%), and high interest in critical thinking-oriented learning (84.00%). From the teachers’ perspective, there was an absolute need (100%) for e-modules that present real-life environmental cases, facilitate collaboration, provide clear problem-solving steps, and integrate multimedia elements. These findings highlight a gap between existing learning conditions and the expectations of interactive, student-centered, and contextual learning. In conclusion, the development of a CPS–EIS-based e-module is strongly needed as an innovative solution to support meaningful learning, bridge theory and real-world environmental issues, and enhance students’ critical thinking skills in the digital era.